Correlating whale strandings with Navy exercises off Southern California - Filadelfo, R.; Pinelis, Y.; Davis, S.; Chase, R.; Mintz, J.; Wolfanger, J.; Tyack, P.; Ketten, Darlene; D’Amico, A. (Western Illinois University Regional Center, 2009)
There have been several incidents when Navy sonar operations at sea coincided in time and location with the mass stranding of marine mammals, particularly beaked whales. Filadelfo et al. (this issue) compiled historical data on large-scale naval exercises and found significant correlations with whale mass strandings in some locations but not in others. In the present study, we compile information on Navy operations off southern California and single strandings of several cetacean species to see if there is a correlation between strandings and Navy exercises in this area. We use information on the state of decomposition of the stranded animals to treat the actual time of stranding as a random variable, and we simulate the correlation between Navy activity and strandings with a Monte Carlo model. For gray whales (Eschrichtius robustus), the 95% confidence interval (CI) for the ratio of odds of a stranding occurring as a result of Navy exercises to the odds of a stranding occurring naturally was (0.879, 1.582), consistent with the null hypothesis of no difference in stranding rates between times of Navy exercises and other times. For other species, the 95% CI for the odds ratio was (0.716, 1.394), which is, again, consistent with the null hypothesis.